PENGUATAN NILAI MORAL SEBAGAI STRATEGI PENCEGAHAN BULLYING MELALUI PROGRAM EDUKASI PADA SISWA SMA - Elysa Rohayani Hsb, Asriani Hasibuan, Harry Sambayu, Derliana Hasibuan, Dharyana Suryadijaya, Laili (JURNAL BIMA, 2026)
Bullying in schools remains a serious issue that affects student’s psychological wellbeing, academic performance, self-confidence, empathy and moral values which should ideally develop optimally so it is very important to a comprehensive strategy to help teenager to repair an affect and their moral to understanding cultural diversity and positive contribution. Therefore the community Service (PKM) is used an effort to strengthen moral values as a strategy to prevent bullying. The community service method used was a descriptive qualitative approach. The subject in community service were students in grade XI and XII Mas Al-Ittihad Aek Nabara. The data collection techniques is observation, discussion and question answer. The result of this community service showed that indicate an improvement in students' understanding of the definition of bullying, its various forms, and its negative impacts. Furthermore, students demonstrated increased awareness of the importance of empathy, tolerance, and mutual respect as efforts to prevent bullying. Consequently, this educational program through character education is effective in supporting the creation of a safe, comfortable, and conducive school environment for the learning process.